PENGARUH PASAR MODAL AMERIKA TERHADAP PASAR MODAL LIMA NEGARA ASEAN PADA KONDISI: SEBELUM, SAAT, DAN SESUDAH KRISIS SUBPRIME MORTGAGE - Budi Setiawan; Taufik . (Program Studi Magister Manajemen FE Unsri, 2016)
This study is conducted to determine the impact of U.S. stock market on ASEAN five stock markets before, during, and after subprime mortgage crisis. The data is composed of daily closing stock price over the period from January 1st 2000 – June 1st 2007 (before crisis), June 2nd 2007 – April 2nd 2009 (during crisis), and April 3rd 2009 – December 31st 2014 (after crisis). The research methodology employed includes linear regression and chow test. The results of this study reveal evidence that U.S. stock market significantly give the positive effect on ASEAN five stock markets before, during, and after subprime mortgage crisis. Chow test result showed that there are differences of influence among U.S. stock market and ASEAN five stock markets before, during, and after subprime mortgage crisis. For further research can add other Asia stock markets such as Nikkei225 Index (Japan), Hang Seng Index (Hong Kong), Kospi Index (South Korea), and BSE Index (India)